SIFAT PAPAN SEMEN SABUT KELAPA - Rozak Memed; Paribotro Sutigno; I M Sulastiningsih (Jurnal Penelitian Hasil Hutan, 1984)
The report  deals  with  laboratory  tests  on  the properties   of cement board  made  from   coconut husk bonded  with  Portland  cement. The test  includes  board  density,   moisture   content.   thickness reduction due to  and bending strength.The  result reveals that the physical   and  mechanical  properties   of  cement  board  made   with  Ca(OH)2 and K2SO4) Al2 (S04)3 mineralizing fluid produces  better  quality  board  compared with that using CaCl2. The physical  and mechanical  properties   of cement boards  with  Ca(OH)2 and  (K2SO4) Al2  (S04)3   conform   to  the  DIN 1101 standard. The bending  strength  of cement  board  made with CaCl2 does not conform  to the DIN 1101 standard.